ANALISIS PEMECAHAN MASALAH MATEMATIKA DALAM MENINGKATKAN NUMERASI SISWA KELAS II SDN PLAMONGANSARI 02 SEMARANG - Setianingtyas, Rustanti; Listyarini, Ikha; Nuvitalia, Duwi; Sugianti, Kristiani Rina (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
The purpose of this study is to analyze mathematical problem solving in improving the numbering of students of the secon grade at SDN Plamongansari 02. This research method uses qualitative research with a descriptive approach involving observation, interviews and documentation. Based on the results of the research and discussion, it shows that the stages of solving mathematical problems which include understanding the problem, planning, explanation, implementing the plan, checking the results again, so that the numeracy results where class II students at SDN Plamongansari 02 obtained the highest score of 90 and the lowest was 50 with an average of 76. the number of students was 28 students. Apart from that, it was influenced by the factors involved such as student involvement, support from students, and learning media. So it can be concluded that solving mathematical problems is an effective strategy in completing numeracy and is also one of the factors that determine the numeracy success of class II students at SDN Plamongansari 02 Semarang and it is recommended to integrate this approach in daily learning.